Current state of knowledge and information sharing among home healthcare professionals involved in heart failure management. Issue 3 (March 2023) - Shimomoto, Rie; Kubo, Toru; Yamanaka, Fukuko; Tsuchihashi-Makaya, Miyuki; Suganuma, Narufumi; Kitaoka, Hiroaki
Abstract: Background: The current state of knowledge related to disease management of heart failure (HF) and information coordination practices provided by non-physician healthcare professionals such as nurses and therapists working at home-visit nursing stations in Japan are not well known. Methods: A questionnaire survey of healthcare professionals working at home-visit nursing stations was conducted in Kochi Prefecture. Data collected from 151 nurses and therapists were analyzed. Results: Regarding the basic characteristics of the respondents, the majority were in their 30s and 40s, and approximately 75 % were nurses. In terms of HF knowledge, 53.7 % of respondents said that they "knew" about the New York Heart Association classification. A total of 40.0 % of respondents said that they were "aware of the existence of the HF handbook", and only 29.3 % of respondents said that they "knew" the classification of HF stages. When they were asked about their level of satisfaction related to all medical information provided by the hospital and hospital wards, no one was "very satisfied", and the most common response (66.2 %) was "not very satisfied". In the essential medical information that respondents wanted to obtain from hospitals and hospitals wards for managing HF patients at home, "medication at discharge", "current medical history", "fluid intake and restrictions", "symptoms, signs, and response to exacerbation", and "ideal body weight" were the top five contents. Conclusion: In the cross-sectional study targeted healthcare professionals working at home-visit nursing stations in Kochi Prefecture, the current state of knowledge related to HF and information coordination practices among healthcare professionals were not fully satisfactory in HF management. It is necessary to increase educational opportunities regarding HF for them and further promote information sharing. Graphical abstract: Unlabelled Image Highlights: A questionnaire survey at home-visit nursing stations regarding heart failure (HF) management Of the respondents, 40 % recognized the existence of the HF handbook. Fewer than 30 % of the respondents knew the classification of HF stages. Information coordination practices were not fully satisfactory in HF management.